Total Workload for Radioactive Facilities with Volumetric Modulated Arc Treatment (Brazilian Journal of Radiation Sciences, 2019)
In recent years, there have been major changes in radiotherapy, particularly in dose delivery for treatments using the techniques of Three-Dimensional Conformal Radiation Therapy (3D-CRT), Intensity-Modulated Radiation Therapy (IMRT) and Volumetric Modulated Arc Therapy (VMAT). However, in the literature, no workload results for radiation therapy treatments performed exclusively with the VMAT technique were found. In this study, a new workload and a new VMAT factor will be proposed. For such, patient data originating from management and planning systems were acquired, such as dose values, monitor units, numbers of arcs per patient and number of hypofractionated treatments. The average clinical workload values for conventional treatments were 328 Gy/week, resulting in a VMAT factor of 1.97; similarly, for hypofractionated treatments, the clinical workload was 33Gy/week and the VMAT factor was 1.54. The total workload has a value of 596 Gy/week, less than the value used in the facility shielding design, 1250 Gy/week, and the average value of VMAT factor for conventional and hypofractionated treatments showed that a smaller amount of C should be used at facilities that perform exclusive VMAT treatment.